What is the impact of a capital structure change on firms' human capital? - Videira, Ana Beatriz Guedes (2016)
The aim of the present dissertation is to understand how changes in Capital Structure impact firms’ Human Capital, focusing essentially on average employees’ wages. To gauge this impact, it is analysed an unbalanced panel from the Euronext-100 Index, comprising a sample of 71 firms for the period 2000 to 2015. The empirical results using 1-year independent lagged variables, with fixed-effects model specifications, indicate that: i) Capital structure changes, leading to leverage increases, make employees worse off, implying wage reductions; ii) Distressed firms pay higher wages to their employees; iii) Firms within Labor Intensive industries pay higher wages than those within Non-Labor-Intensive industries; and iv) Wages are lower within countries providing higher average unemployment benefits. This study adds to the existing literature for two reasons: i) It tests the existing academic evidence regarding the relation between leverage and human capital for the European case, revealing that the positive effect usually found in the literature does not hold here; and ii) It reinforces the theoretical prediction that labor costs can be considered as a debt limiter.